Synthesis of Ni nanoparticles with controllable magnetic properties by atmospheric pressure microplasma assisted process. Issue 5 (22nd December 2017) - Lin, Liangliang; Li, Sirui; Hessel, Volker; Starostin, Sergey A.; Lavrijsen, R.; Zhang, Wei
Abstract : An atmospheric pressure microplasma technique is demonstrated for the gas phase synthesis of Ni nanoparticles by plasma‐assisted nickelocene dissociation at different conditions. The dissociation process and the products are characterized by complementary analytical methods to establish the relationship between operational conditions and product properties. The innovation is to show proof‐of‐principle of a new synthesis route which offers access to less costly and less poisonous reactant, a higher quality product, and a simple, continuous and pre/post treatment‐free manner with chance for fine‐tuning "in‐flight." Results show that Ni nanoparticles with controllable magnetic properties are obtained, in which flexible adjustment of product properties can be achieved by tuning operational parameters. At the optimized condition only fcc Ni nanoparticles are formed, with saturation magnetization value of 44.4 mAm 2 /g. The upper limit of production rate for Ni nanoparticles is calculated as 4.65 × 10 −3 g/h using a single plasma jet, but the process can be scaled‐up through a microplasma array design. In addition, possible mechanisms for plasma‐assisted nickelocene dissociation process are discussed. © 2017 The Authors AIChE Journal published by Wiley Periodicals, Inc. on behalf of American Institute of Chemical Engineers AIChE J, 64: 1540–1549, 2018